The impacts of labor market policies on job search behavior and post-unemployment job quality - Simen Gaure; Knut Røed; Lars Westlie (Institute for the Study of Labor (IZA), 2008)
We examine empirically the impacts of labor market policies - in terms of unemployment insurance (UI) and active labor market programs (ALMP) - on the duration and outcome of job search and on the quality of a subsequent job. We find that time invested in job search tends to pay off in the form of higher earnings once a job match is formed. More generous UI raises expected unemployment duration, while improving the quality of the resultant job. Participation in ALMP raises the probability of finding a job and the level of expected earnings, but at the cost of lengthening job search.
urn:nbn:de:101:1-20081126775
Keywords: C14; 330; Multivariate hazards; job search; job quality; timing-of-events; NPMLE; MMPH; Arbeitsmarktpolitik; Arbeitsplatzsuchmodell; Arbeitsbedingungen; Lohnniveau; Norwegen